2000
DOI: 10.1046/j.1439-0418.2000.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term developments in the carabid and staphylinid (Col., CArabidae and Staphylinidae) fauna during conversion from conventional to bilogivcal farming

Abstract: In two field experiments over periods of 6 and 8 years the activity density and diversity of carabids and staphylids were measured in pitfalls traps during the conversiion fron conventional to biological farming. Positive effects of the conversion were observed for many carabid species; among them Harpalus rufipes and several Amara, Bembidion and Pterostichus species, and the staphylinid fly parasitoid Aleochara bipistulata. The increased number of weed species present could at least partly explain the rise. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 13 publications
(16 reference statements)
0
35
0
3
Order By: Relevance
“…Purtauf et al (2005) found no difference in carabid species richness or activity density between organic and conventional farms. However, Andersen and Eltun (2000) found H. rufipes increased with organic conversion. It is primarily a seed predator, notably of grass seeds, and the increase in grassland might explain the increased catch numbers.…”
Section: Discussionmentioning
confidence: 90%
“…Purtauf et al (2005) found no difference in carabid species richness or activity density between organic and conventional farms. However, Andersen and Eltun (2000) found H. rufipes increased with organic conversion. It is primarily a seed predator, notably of grass seeds, and the increase in grassland might explain the increased catch numbers.…”
Section: Discussionmentioning
confidence: 90%
“…Although many authors studied the European staphylinid fauna (Galli 1985;Reede 1985;Dennis et al 1990;Majzlan and Holecová 1993;Wardle et al 1993;Heyer 1994;Krooss and Schaefer 1998;Andersen 1991Andersen , 2000Perner and Malt 2002), it is still little known about their community structure in agro-ecosystems. Andersen (1991) presented a list of staphylinid beetles occurring in spring barley, cabbage, carrot, potato, strawberries and grassland fields in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Aloconota gregaria (Erichson), Anotylus rugosus (F.) Atheta fungi (Gravenhorst), Amischa analis (Gravenhorst), Tachinus signatus (Gravenhorst) and Philonthus cognatus (Stephens) were most often found. Data about Staphylinid beetles from cereal ecosystems in Europe are frequent (Dennis et al 1990;Krooss and Schaefer 1998;Andersen 2000;Perner and Malt 2002). In wheat the most abundant species were Philonthus cognatus (Stephens), Tachyporus hypnorum (F.), T. chrysomelinus (L.), T. obtusus (L.) and Stenus biguttatus (L.).…”
Section: Introductionmentioning
confidence: 99%
“…Orientation of their studies can bee divided in several directions: (1) study of population and community structure in different crops (Skuhravý & Novák 1957;Skuhravý et al 1959;Štepanovičová & Beláková 1960;Štusák 1962;Petruška 1966Petruška , 1971Petruška , 1986Petruška , 1987Petruška , 1988Obrtel 1969;Novák 1972;Andersen 1999a;Basedow et al 1976;Sekulić et al 1973;Ericson 1978;Sharova 1983;Honěk 1997;Petřval-ský & Porhajašová 2002, Porhajašová 2002, (2) study of influence of different pest control, fertilization or cultivation practices and pollution (Pauer 1975;Šustek 1985, 1990, 1994aLővei 1984;Purvis & Currey 1984;Kabacik-Wasilik 1986;Kromp 1989Kromp , 1990Fadl et al 1996;Pavuk et al 1997;Andersen 1999b;Andersen & Eltun 2000) or (3) study of influence of landscape vegetation spatial structure on fauna in neighboring fields (Boháč & Pospíšil 1984;Gruttke 1991;Kromp & Steinberger 1992;Šustek 1992, 1994b. Influence of input of manure or slurry on field ground beetle fauna was studied by Kabacik-Wasilik (1986), Purvis & Currey (1984), …”
Section: Introductionmentioning
confidence: 99%